2018
DOI: 10.19084/rca17339
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic characterization of forage legumes root nodule bacteria isolated from semiarid region in Brazil

Abstract: Forage legumes are important resources in semiarid regions due to their abilities to adapt to soils with low fertility and fix nitrogen when associated with diazotrophic bacteria. Here, we applied a polyphasic approach to characterize a set of legume nodule isolates obtained from Clitoria ternatea and Stylosanthes capitata cultivated in the soils of a semiarid region of Brazil. A total of 126 bacterial isolates were obtained: 45 isolates from C. ternatea and 81 isolates from S. capitata. Nodulation tests revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…The use of this strategy fits to the selection of bacterial isolates for biotechnological applications as inoculants, due to the increasing of the selection of putative rhizobial over the non-rhizobial strains. In our collection, we obtained a total of 64% of all slow growing isolates as positive for nodC amplification, with 161 positive isolates, in agreement to the isolation of non-rhizobial isolate from nodules in the Brazilian semiarid region (Nunes et al 2018) and in African continent (Mohammed et al 2018).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The use of this strategy fits to the selection of bacterial isolates for biotechnological applications as inoculants, due to the increasing of the selection of putative rhizobial over the non-rhizobial strains. In our collection, we obtained a total of 64% of all slow growing isolates as positive for nodC amplification, with 161 positive isolates, in agreement to the isolation of non-rhizobial isolate from nodules in the Brazilian semiarid region (Nunes et al 2018) and in African continent (Mohammed et al 2018).…”
Section: Discussionsupporting
confidence: 74%
“…As well as observed to the B. vignae related bacteria, the affiliation of ESA 367 indicates that this strain can be member of a new species within Microvirga genus. In addition to M. vignae, other members of Microvirga genus had been recently isolated from soils of the São Francisco River Valley, region where the municipality of Juazeiro is located (Nunes et al 2018;Oliveira et al 2020), showing that members of nodulating clade of Microvirga genus are widespread in these soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the São Francisco River Valley, isolates of cowpea-nodulating Microvirga spp. were already isolated (Nunes et al, 2018). In the same basin, the type strain BR 3299 T of M. vignae was isolated in 1996 and the species was described in 2014 (Radl et al 2014), indicating that nodulating Microvirga spp.…”
Section: Discussionmentioning
confidence: 89%
“…A collection of 75 isolates was obtained from the root nodules of five acacia species from south-western Saudi Arabia and characterized by a polyphasic approach (Nunes et al 2018) including phenotypic, genotypic, and phylogenetic analyses. The results of the plant nodulation tests showed that the majority of isolates were able to nodulate their host of origin.…”
Section: Discussionmentioning
confidence: 99%